Mapping development potential of dry-season small-scale irrigation in Sub-Saharan African countries under joint biophysical and economic constraints: An agent-based modeling approach with an application to Ethiopia - Xie, Hua; You, Liangzhi; Dile, Yihun T.; Worqlul, Abeyou W.; Bizimana, Jean-Claude (Elsevier, 2021)
Sub-Saharan Africa has long been beset with food insecurity. Investment in small-scale irrigation may provide a solution to address the challenge by extending crop production into the dry season. We present an agent-based modeling system to assess the potential of dry-season small-irrigation development in Sub-Saharan Africa with an application to Ethiopia. We identify significant potential for investing in dry-season small-scale irrigation in Ethiopia and map geographic domains with highest investment opportunities.